LINGUACULTURAL AND LINGUAPERSONAL ANALYSIS OF RELIGIOUS CONCEPTS IMPLEMENTATIONS IN RUSSIAN CREOLISED CARTOONS - Maria A Belova (Russian Language Studies, 2017)
The article attempts to cover problems of religious concepts implementation by verbal and iconic symbols in ironic texts. The paper is devoted to definition of the correlation between the components of religious creolised texts and national linguaculture. Relevance of a research is defined by a rate of such texts in media and ambiguity of their misinterpretation both by the recipients learning Russian and Russian natives. The use of nonverbal sources gives to the recipient more freedom for decodingthat sometimes leads to negative consequences. Worldwide scandals anyhow related to caricatures (mostly, anticlerical) became more frequent. To Rosse Flemming, the editor of the Danish newspaper “Jyllands-Posten”, in the book “Case of caricatures of the prophet Muhammad” tells that he couldn’t imagine the role of future world crisis when in September, 2005 granted he gave his permission for the publishing twelve cartoons of the Muslim prophet [1]. In 2005 even more tragic event took place in Paris. Shooting at publishing house of the French comical newspaper of Charlie Hebdo was followed by lots of pros and cons of creativity of the killed authors. Such sharpness increases scientific interest to this area. There is a range of new papers devoted to studying of a phenomenon of a caricature, the description of the principle of its impact on recipients, setting standards of ethics and morals in the genre. The diachronic description of verbal representors of a concept of religion that express irony allows tracking changes in the modality of Russian natives.